High-Resolution Distributed Dispersion Characterization for Polarization Maintaining Fibers Based on a Closed-Loop Measurement Framework - Zhangjun Yu; Jun Yang; Yonggui Yuan; Feng Peng; Hanyang Li; Changbo Hou; Chengcheng Hou; Zhihai Liu; Libo Yuan (IEEE Photonics Journal)
A closed-loop dispersion measurement framework (CLDM) is proposed. Carrying out dispersion compensation with an arbitrary trial dispersion on the interferogram under test, and using a criterion function as feedback to adjust the trial dispersion until the optimum is reached the trial dispersion is the measured result. The CLDM framework is not only noise-robust but can also cope with the case of multiple peaks that provides high resolution. We use it to measure the distributed birefringence dispersion (BD) chromatic dispersion difference of the two polarized modes of polarization maintaining fibers (PMFs). In this regime, the optimum of dispersion compensation is that the signal energy of every peak in the interferogram is concentrated. Thus, we present a criterion function to evaluate the signal energy concentration. Theoretical and experimental demonstration of this method is implemented. In addition, the spatial resolution ( $<$ 10 cm) is discussed. Eventually, a $≈$ 3 km-length PMF coil is tested. The measurement error for BD and its slope @1550 nm are $<5\;×\; 10^{-4}$ ps/nm/km and $2\;×\; 10^{-4}$ ps/nm $^2$ /km, respectively.